4‐aminobenzensulphonate‐assisted enhanced hydrophily of carbon nanotubes and simultaneous uniform dispersion of PtRu nanoparticles. (1st May 2018) - Wu, Bohua; Zhu, Jiajin; Yin, Siyuan; Li, Xue; Chu, Jia; Xiong, Shanxin
Abstract : A 4‐aminobenzensulphonate (p‐ABS)‐assisted strategy has been proposed to separate the aggregations of carbon nanotubes (CNTs) and deposit PtRu nanoparticles on them with holonomic graphitic structures. In this work, as an efficient dispersing agent, 0.5 wt% of p‐ABS in isopropanol/water solution can drastically separate CNTs aggregations. Meanwhile, under the help of p‐ABS, high dispersion of PtRu nanoparticles is anchored on CNTs surface with small average diameter (3.0 ± 0.5 nm). It is clear that p‐ABS acts as dispersant, stabiliser and linker in the proposed strategy. The obtained PtRu/p‐ABS‐CNTs nanohybrids were applied as electrocatalysts for methanol oxidation and showed enhanced catalytic activity and stability. Due to the introduction of the amino (−NH2 ) and sulphonic acid (−SO3 H) groups onto CNTs by non‐covalent method, it ensures PtRu nanoparticles with the advantages of high dispersion, small particle size, locating in triple‐phase zones to increase Pt utilisation and reduces the electrochemical corrosion of p‐ABS‐CNTs, which result in the improved catalytic performance. This work demonstrates an alternative approach to fabricate CNTs supported superior noble metal catalysts for broad applications in fuel cells and chemo/biosensors.